Analytical and experimental study of a reverse circulation drill bit with an annular slit. (September 2016) - Cao, Pinlu; Chen, Yunwang; Liu, Miaomiao; Chen, Baoyi; Wang, Jinsong
A new type of drill bit designed with an annular slit was developed to enhance the reverse circulation effect of the down-the-hole hammer drilling technology. A computational fluid dynamics code, Fluent, was used to simulate the flow phenomena inside the drill bit. The simulation results show that the air flowing through the annular slit moves upward along the wall of the central passage of the annular drill bit and that there is no interference phenomenon similar to the normal drill bit, which is beneficial for the formation of reverse circulation. Meanwhile, the new drill bit with the annular slit was produced and tested in the laboratory. The results show that for the annular drill bit with the flushing nozzles closed, the mass flow rate of the sucked air is approximately 63.78 g/s, which is 1.76 times that of the normal drill bit, while it is about 2.46 times if the flushing nozzles are opened. In addition, many factors can affect the reverse circulation effect of the annular drill bit, including the slit width, the distance between the annular slit and the working surface of the drill bit, and the flow direction of the gas ejected from the annular slit.